Conceptual and terminological aspect of the practice of revelation of thoughts in the tradition of Egyptian and Palestinian monasticism of the 4th — 7th centuries - Fadeev, Alexander (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2024)
The article analyzes the original terminology of the patristic writings of Egyptian and Palestinian monasticism of the 4th - 7th centuries, which is found when mentioning the practice of revelation of thoughts as an important pastoral-ascetic activity and a form of spiritual leadership in the monastic tradition of this period. The author identifies the main terms related to this area, analyzes the context of their use and various semantic shades that reflect the corresponding forms, conditions and characteristics of this activity. Modern patrolologists strictly distinguish the practice of revealing thoughts from confession, which in ancient times was carried out in all forms of monastic life: hermitage, semi-hermitage, community and laura. At the same time, the most ancient sources do not always reflect this difference, their external forms and ideological content. Another equally important question remains not entirely clear: how the great fathers of ancient Eastern monasticism understood this saving remedy, whether for them there was a division between confession and revelation of thoughts as between two different actions of repentance, and if so, what appeared for them clear criteria for such division. The sources for the study were the most famous and significant works of monastic writing in the tradition of Egypt and Palestine in the 4th - 7th centuries, as the period of formation, development and greatest flowering of monasticism, and at the same time its ascetic and pastoral theology. Some manuscripts of individual sources were also used as sources, including the most ancient ones, reflecting the understanding of the practice being studied in the minds of scribes belonging to various manuscript traditions - Greek, Latin and Coptic. The subject of study are terms denoting revelation (of hidden thoughts, sinful falls committed in secret), revelation (of oneself, one’s emotional experiences, demonic temptations, etc.), confession (of sins, a passionate disposition of the soul and its destructive consequences), etc.